Sayed`s Theory in Quantum Mechanics: An Innovative Approach for Wave Function Equations Measurability, Efficacy and Universality - El-Mongy, Sayed A. (JOURNAL OF ADVANCES IN PHYSICS, 2024)
Allah (God) is ubiquitous and the only Creator of Everything. Quantum mechanics is the world of the microscopic scale of physics. The universe is a macroscopic manifestation of the quantum approach. In this revolutionary article, correctness and rectification of Schrodinger wave equations that has huge limitations and shortcomings, were proudly achieved. The Sayed quantum wave function (SQWF) was derived and defined (Ψs) for free electron and in Laplace coordinates as a function in wavelength and light speed. The SQWF was calculated and quantified for de Broglie moving electron; 0.4033x10-20 Second. Using SQWF equation, the speed of light was accurately calculated; 3x108 m/s. respectively. An outstanding Sayed`s quantum wavelength (SQW) was proposed and elucidated. The Sayed time dependent wave function equations (STDWFE) were derived and given to be a generic alternative to deal with all atoms rather than the one electron atoms of Schrodinger. The crucial parameters; wavelength, Rydberg constant RH, atomic number, principle quantum number, and mc2 were introduced in the STDWFE. It is a quantized formula. The (Ψs) was calculated for H, He, B and found to be , ,The Sayed quantum constantRH mc2, was quantified to be 8.93x10-7 J/m.